Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1089/sur.2011.114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of New Anti-Adhesion Polyvinyl Alcohol Gel on Healing of Colon Anastomoses in Rats

Abstract: This experimental study showed no significant differences in anastomotic leakage, anastomotic bursting pressure, or collagen content of the anastomosis when using the adhesion barrier polyvinyl alcohol around colonic anastomoses. The barrier did not prevent adhesion formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…The promising efficacy demonstrated by the A-Part Ò hydrogel in this experiment stimulated us to investigate this product further, focusing on its safety when applied around an intestinal anastomosis and in the presence of synthetic material such as intra-abdominally placed meshes [33]. The promising experimental results also led to initiation of a clinical trial of the safety and efficacy of the hydrogel [34].…”
Section: Discussionmentioning
confidence: 91%
“…The promising efficacy demonstrated by the A-Part Ò hydrogel in this experiment stimulated us to investigate this product further, focusing on its safety when applied around an intestinal anastomosis and in the presence of synthetic material such as intra-abdominally placed meshes [33]. The promising experimental results also led to initiation of a clinical trial of the safety and efficacy of the hydrogel [34].…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, it could be shown that there was no difference in tissue qualities regarding tensiometry-induced tissue rupture comparing test and control groups; however, once more splenomegaly was identified in the rabbit end-to-end anastomosis model, being related to phagocytosis of the PVA/CMC material. In contrast to rats [30,31,32,33], rabbits seem to be more sensitive to resorption and excretion of PVA/CMC gel. Therefore, the rabbit abdominal wall model as well as the rabbit anastomosis model treated with PVA/CMC gel indicate a limited and adjusted dosage before internal use, suggesting a dosage <2 ml PVA/CMC gel per kg body weight per rabbit and indicating the necessity of a careful adjustment of the dosage in human clinical studies as well.…”
Section: Discussionmentioning
confidence: 95%
“…Medical devices, such as adhesion-preventing agents, must fulfill extensive requirements regarding biocompatibility, safety and efficacy before their admission into common practice [[35], FDA Guidance for resorbable adhesion barrier devices for the use in abdominal and/or pelvic surgery: guidance for industry]. Different study groups have shown the positive anti-adhesion properties of PVA/CMC membranes and gels in different and complex animal models [32,33,37]. Despite the fact that PVA and CMC are commonly used substances for topological medical use, little is known about their internal reactions in the body, although the clearance of PVA out of the body has been described accurately [38].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations